DEVELOPMENT, ESSENCE AND SCOPE OF APPLICATION OF STRUCTURAL AND CABLE-STAYED COMPOSITE STRUCTURES - Gasii, G. M. (Science and Transport Progress, 2017)
Purpose. In construction there is a need to create new structures, including spatial coverage systems, the use of which will save materials and reduce the complexity of assembling processes and manufacturing. Summarizing the results of preliminary theoretical study of existing types of spatial structures, purpose of the article is to find perspective directions for the development of new structures, which would be deprived of the drawbacks of analogues while ensuring the economic effect due to the rational use of materials and energy saving. Methodology. To achieve this purpose, the research of constructive solutions of various spatial systems was carried out. There were analyzed domestic and foreign patent databases and the results of experimental tests and theoretical studies. Findings. The main stages of development for a new type of spatial structure (spatial structural and cable-stayed composite structure) are highlighted. Information on the features of its structure is given. Spatial structural and cable-stayed composite structures are a completely new type of spatial bearing systems, which, due to the original constructive decision, have a wide field of application. The basic element of created structures is the modular element that has the shape of a thorough pyramid and consists of a plate and tubular rods. Modular elements are manufactured in factories. Straight and curved structures, as well as various bearing systems and their combinations can be made of modules. Originality. The author has formulated a concept of original constructive forms and their supporting elements. New types of spatial structural and cable-stayed composite structures for buildings and constructions of different purposes were proposed and created. Practical value. Designed cable-stayed structures have a wide field of application, they can be used for industrial and civil construction. The use of created structures in the construction of buildings and structures can provide a significant economic effect due to the rational use of materials and energy saving at the stage of manufacturing and installation.